HEADWAY TEST AS AN ALTERNATIVE ONLINE ENGLISH PROFICIENCY TEST: INDONESIAN EFL TEACHERS’ PERCEPTION - Tenny Murtiningsih (UMBanjarmasin, 2021)
Teaching learning process mostly has used online method since Covid-19 pandemic. It happens also in language assessment. Language assessment must be given by online to prevent the spread of Covid-19. Giving online English Proficiency Test is one of the examples. HeadWay Test is as one of English Proficiency Tests designed to answer this needs. Actually, HeadWay Test has been used for language assessment since 2010. It was before this pandemic happens. This research is qualitative research. It describes teachers’ perception of the using of online HeadWay Test. It invited 58 English teachers from teacher association in South Kalimantan as the participants. In this case, they were given online HeadWay Test firstly. Then, the researcher gave them the questionnaires. There were 12 questions to answer in the questionnaire. The question asked about what their perception after they took online Headway Test. Generally, the result of this questionnaire showed that they have good perception of online HeadWay Test. They claimed that online HeadWay Test can be used as an alternative of online English Proficiency Test.